Efficacy of Mouth Rinses Against SARS-CoV-2: A Scoping Review - Ather, Amber; Parolia, Abhishek; Ruparel, Nikita B. (Frontiers in Dental Medicine, 2021)
Introduction: The presence of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in saliva and nasopharyngeal secretions has challenged the routine practice of dentistry. Use of pre-procedural mouth rinses has been recommended by several organizations to potentially reduce the transmission of SARS-CoV-2. This scoping review aimed at evaluating the available evidence on the efficacy of mouth rinses against SARS-CoV-2. Methods: A thorough literature search on electronic databases (PubMed, Scopus, and Google Scholar) was performed by two independent reviewers and data from articles addressing the aim of this paper were extracted. Results: After exclusion of articles not addressing the end point in question, 12 articles were included in this scoping review. Out of the 12 articles, 7 were in vitro studies and 5 were in vivo human clinical studies. The in vitro studies used a standardized methodology (Endpoint dilution assay) to evaluate the efficacy of antimicrobial mouth rinses against SARS-CoV-2. The in vivo studies were done utilizing Polymerase chain reaction (PCR) assay of samples obtained from saliva or nasopharyngeal swab or a combination of both nasopharyngeal and oropharyngeal swab. The reagents tested in these studies included povidone-iodine, chlorhexidine, hydrogen peroxide, essential oils, and quaternary ammonium compounds and demonstrated varied efficacy against SARS-CoV-2. Conclusion: Based on the available evidence from in vitro studies, it can be concluded that mouth rinses have a potential to reduce SARS-CoV-2 viral load; however, effectiveness in in vivo conditions is still inconclusive. Owing to the substantial heterogeneity in reporting of the anti-SARS-CoV-2 efficacy of mouth rinses, this review highlights the need to conduct future research with robust and standardized methodologies to confirm effectiveness of mouth rinses.